Direct Observation of the Gating Step in Protein Electron Transfer: Electric-Field-Controlled Protein Dynamics - Kranich, Anja (2008)
Heterogeneous electron transfer of proteins at biomimetic interfaces is characterized by unusual distance dependences of the electron-transfer rates, whose origin has been elusive and controversial. Using a two-color, time-resolved, surface-enhanced resonance Raman spectroelectrochemical approach, we have been able to monitor simultaneously and in real time the structure, electron-transfer kinetics, and configurational fluctuations of cytochrome c electrostatically adsorbed to electrodes coated with selfassembled monolayers. Our results show that the overall electron-transfer kinetics is determined by protein dynamics rather than by tunnelling probabilities and that the protein dynamics in turn is controlled by the interfacial electric field. Implications for interprotein electron transfer at biological membranes are discussed.